Assessment of greenness for solid phase microextraction techniques of sample preparation for flavors by AGREE Prep & SPMS tools - Ruchita Rajput; Sonal Desai (Green Analytical Chemistry)
Assessing the greenness of sample preparation techniques is essential due to the use of various solvents, chemicals, reagents, sorbents, pH adjustments, and energetic inputs. Solid-Phase Microextraction (SPME) is preferred over traditional flavor extraction methods such as Simultaneous Distillation Extraction (SDE) and Solvent-Assisted Flavor Evaporation (SAFE) because of its sensitivity, efficiency, speed, versatility, and economy. SPME fibers coated with stationary phases can extract volatile and semi-volatile flavor compounds from food samples, which are then desorbed and analyzed by Gas Chromatography-Mass Spectrometry (GC–MS). This article provides an assessment of the greenness of 50 SPME techniques for flavor analysis using the AGREE Prep and Sample Preparation Metric of Sustainability (SPMS) tools. This evaluation offers valuable insights into the environmental impact and sustainability of SPME as sample preparation techniques for flavour analysis. As per AGREE Prep, method 34 was found to be environmental friendly with score of 0.66, attributed to safe solvents, minimized waste, high sample throughput, and low energy consumption where as method 7 with SPMS scores of 7.05 is more sustainable due to miniaturization, fewer steps, and low energy use.